A new species of Ceraticelus Simon from southern California and a redescription of Ceraticelus phylax Ivie & Barrows, its probable sister species (Araneae: Linyphiidae) - Prentice, Thomas R.; Redak, Richard A. (Zootaxa, 2009)
A new species of Ceraticelus Simon, 1884 from southern California is described, Ceraticelus artemisiae sp. nov. Its probable sister species, Ceraticelus phylax Ivie & Barrows, 1935, a potential adventive species with which it now often co-occurs in southern California, is redescribed for the first time. We provide detailed descriptions of both species because an adequate definition of the genus is lacking and the conformation of the male Ceraticelus palpal bulb has been only superficially treated. We also provide a definition of Ceraticelus based on examination of specimens of the type species, Ceraticelus fissiceps (O. P.-Cambridge). Problems associated with both the conformation of the male bulb and the paracymbium morphology are discussed. Despite the lack of a phylogenetic analysis of Ceraticelus, we propose that Ceraticelus phylax and Ceraticelus artemisiae sp. nov. are sister species based on shared characters that distinguish them from all other congeners. We suggest that the presence of Ceraticelus phylax in California is the result of incidental introduction rather than natural dispersal. Habitat, distribution, and phenology data are presented in the text. Illustrations and a distribution map are also furnished for both species.